Surgical Treatment of Left Main Coronary Artery Disease Off-Pump CABG is a Good Option (Bangladesh Heart Journal, 2016)
There has been increasing interest in the potential benefit of off-pump coronary artery bypass (OPCAB) surgery when compared to conventional coronary artery bypass (CCAB) using cardiopulmonary bypass (CPB) in the presence of critical left main stem (LMS) Disease. A prospective observational study was conducted from January 2006 to June 2012 in the Department of Cardiac Surgery in the National Institute of Cardiovascular Diseases (NICVD), Dhaka. The study included total 110 patients with LMS disease who underwent CABG. 25 cases were done under CPB and 85 cases were done on beating heart. The two groups had similar baseline characteristics including age, sex, risk-factors, comorbid conditions and extent of coronary artery disease. There was no difference between the groups with respect to mortality, but the incidence of post-operative bleeding (p